ARTiCO - AR in Tissue Converting - PERCOM 2022, Demo Session - Moroni, Davide; Pieri, Gabriele; Tampucci, Marco; Masini, Daniele (Zenodo, 2022)
For fully up-taking the advances achieved in pervasive monitoring systems within Industry 4.0, novel intelligent interfaces are needed to ease interactions with human personnel and enable them to access the available data and services ergonomically. To this end, we present a mobile app based on augmented reality that allows operators to receive location-aware notifications and access and visualize real-time information and guidance for troubleshooting and plant maintenance. The app has been tailored to respond to the needs of a specific scenario, i.e. tissue converting, where it has provided encouraging results.